The effectiveness of applying a visual mental imagery program in developing the skill performance level of karate athletes. - belaid, akil abdkader (sports creativity, 2025)
This study presents a modern technique in the field of cognitive psychology that complements the training process for karate coaches, aiming to improve overall athletic performance and skill development in particular. The study comprised two homogeneous groups: an experimental group and a control group. The researcher implemented a visual-mental training program on an experimental sample of 31 high-level karate athletes specializing in kumite, to determine the effect of this type of training on improving their performance in the Kyakutsuki technique. The results showed a positive correlation between the development of visual-mental training and skill performance among the karate athletes, following a structured and systematic mental training program. This program aimed to develop visual-mental abilities and equip the participants with the necessary knowledge and skills to effectively utilize mental training techniques within the training process. Therefore, the researcher recommends the use of such mental programs to develop athletes' mental abilities and enhance their athletic performance.